Tindak Pidana Cyberbullying oleh Anak dalam Perspektif Undang-Undang ITE dan Sistem Peradilan Pidana Anak - Adwi Mulyana Hadi (Journal of Law, Society, and Islamic Civilization, 2025)
The advancement of information and communication technology has created a new space for acts of violence perpetrated by children, one of which is cyberbullying. This phenomenon is increasingly prevalent among adolescents, who generally lack a comprehensive understanding of legal boundaries in digital behavior. This study aims to analyze cyberbullying committed by minors from the perspective of Indonesian criminal law, particularly in relation to Law No. 1 of 2024 concerning the Second Amendment to Law No. 11 of 2008 on Electronic Information and Transactions (the ITE Law), and to examine the relevance of the restorative justice approach as stipulated in Law No. 11 of 2012 on the Juvenile Criminal Justice System (the SPPA Law). The research method employed is normative juridical with a statutory and case study approach. The findings indicate that cyberbullying acts committed by children may be classified as criminal offenses under Article 27 paragraph (3) and Article 28 paragraph (2) of the ITE Law. However, the imposition of criminal sanctions on minors must consider the principles of child protection and restorative justice as mandated by the SPPA Law. This study recommends the harmonization of the ITE Law and the SPPA Law, as well as the importance of digital legal education within families and schools to prevent the escalation of cyberbullying among minors. Accordingly, the legal approach to juvenile cyberbullying offenders should not solely focus on punishment but also emphasize rehabilitation and equitable social restoration.